Curriculum Management and Educational Assessment At the Master Program in Defense Industry, Defense University, Republic of Indonesia - Susilo Wardoyo; Hanafiah Hanafiah; Sri Handayani (Utan Kayu Publishing, 2024)
This study aims to describe curriculum management and higher education assessment systems in producing quality college graduates. This study used descriptive qualitative methods, and data collection techniques through observation, interviews and documentation studies. Data analysis techniques use data validity tests with source tringulation. The results of the study show that the Curriculum Management and Educational Assessment System in the Master of Defense Industry Study Program of Unhan of the Republic of Indonesia in accordance with curriculum standards and higher education assessment systems through planning, organizing, implementing and supervising refer to the vision, mission and profile of graduates in attitudes, knowledge and skills. The conclusion and suggestion in this study is that curriculum planning and educational assessment systems in the Defense Industry Master Study Program of the Indonesian Defense University are carried out through systematic curriculum design, strict assessment standards, and comprehensive assessment instruments. Curriculum organization involves learning designs prepared by course lecturers, distribution of courses each semester, and assessment instruments applied to each subject. The implementation of the curriculum and assessment system refers to the standards of the learning process and assessment that have been set, including the academic calendar and the schedule of teaching and learning activities of each lecturer. Supervision of the curriculum and assessment system is carried out through lesson plans, supervision, reports on lecturer learning activities, academic and non-academic achievements of students, and comprehensive learning evaluation. Although the curriculum includes aspects of attitudes, knowledge, and skills, the assessment of non-academic skills such as soft skills and character needs to be considered as one of the development areas in the educational assessment system to improve the quality of graduates holistically.Keywords: Curriculum Management, Educational Assessment, Defense University of Republic of Indonesia